Control interno y gestión presupuestaria en la unidad ejecutora 406 Red de Salud Ucayali Contamana 2024 - Ruiz Vasquez, Mirna Abigail (2024)
The purpose of the final report is to determine the relationship between internal control and budget management in Executing Unit 406 Ucayali Health Network – Contamana, 2024, where a basic method, descriptive and correlational level with a non-experimental design was used. Taking 73 workers as the population, a questionnaire was used to collect information. The results show that internal control is regular (26%), due to the lack of promotion of identification, competence and responsibility in the fulfillment of tasks by managers; However, its application of the good governance code is almost always adequate; In addition, plans, programs and projects are usually executed effectively in the organization. For its part, budget management is rated as regular (25%), since it has an established annual spending plan and its activities are aligned with its objectives; Training is provided for better use of resources and periodic internal audits are carried out. However, indicators are rarely established to measure the financial performance of the organization. The statistical analysis found a strong positive relationship between the variables, corroborated by a rho coefficient of 0.834 and a statistically significant significance of 0.000.